Telemedicine – Meaning, Challenges and Opportunities - Ittipong Khemapech (Siriraj Medical Journal, 2019)
Medical service is one of the crucial policies and decent medical service is required by the population in every country. There are three main obstacles which prevent people from obtaining proper medical cares and treatments. First, the deficiency of medical staffs especially physicians which occur even in the developed countries. Second, regarding an important demographic issue, an increase in the number of the elderly makes the medical services more demanding. Finally, geographical aspect also plays a major role in healthcare inequality. The population dwelling in rural or remote areas struggle from accessing proper medical services. Information and communication technologies have become an important infrastructure upon which several domains can build in order to achieve more effective solutions. Integrating such technologies into the medical discipline results in telemedicine which is currently available across the globe. This article describes telemedicine in three key aspects including current state, challenges and opportunities based upon existing studies and implementations.